PREPARASI KARBON BERPORI DARI LIMBAH AMPAS KOPI SEBAGAI MATRIKS PADA PEMBUATAN SLOW RELEASE FERTILIZER - Fakhri Fachreza; Irfansyah Irfansyah; Diana Diana; Nur Indah Fajar Mukti (Eksergi, 2020)
Urea is one of the fertilizers that are widely used in agriculture. However, the absorption efficiency of urea for plants is currently only around 30%. Therefore, to increase its absorption in plants it is necessary to control the release of urea by making it a Slow Release Fertilizer (SRF) fertilizer. The use of SRF is expected to control the release of nutrients according to the time and amount needed by plants. Natural material which has the potential as a matrix of SRF fertilizer is coffee grounds waste. This research produces carbon from coffee pulp waste which can be used as a matrix in the manufacture of urea SRF fertilizer. With the addition of a matrix of coffee carbon is expected to slow the rate of release of urea into nature. So that the process of absorption of urea into plants will be more leverage. Coffee pulp was pyrolysed with pyrolysis temperature variation (400 - 600oC) using ZnCl2 as activator. The iodine number value of coffee grounds carbon produced decreases with increasing temperature. The addition of carbon coffee grounds can inhibit the release of urea from 81.5% to 26% for 30 days.